Development of immunosuppressive methods for gonadal grafting and xenogeneic germ cell transplantation in rainbow trout (Oncorhynchus mykiss) - Yoshinaga, Túlio Teruo (2022)
In the recent years, germ cell transplantation and the testicular tissue grafts have been used as reproductive biotechnology for commercial and endangered fish species. However, when performed in farther-related species, the donor-derived gametes production is lower or does not occur, while allo- and xenogeneic testis grafts are rejected by the host. The use of immunosuppressive treatment could improve this technology, although their effects on fish immunology and reproduction remain poorly understood. In this study, we aimed to evaluate the use of immunosuppressive treatments in xenogeneic germ cell transplantation and testicular allografts in rainbow trout, as well as the side effects of such substances on male reproduction. Rainbow trout transplanted with Atlantic salmon germ cells were treated with tacrolimus through fed. Our results demonstrate that the administration route used was not able to sustain immunosuppression in the fish larvae, and animals that presented high expression of immune-related makers expression presented lower germ cell counts at the end of the treatment. In addition, tacrolimus treatment did not affect donor-derive spermatozoa production of transplanted animals. Moreover, an immunosuppressive therapy composed by tacrolimus and mycophenolate mofetil mixture demonstrated immunosuppressive effects and reduced acute inflammation in subcutaneous testis allografts in rainbow trout. Nevertheless, histological, and qRT-PCR analysis revealed that allografted testis were severed damaged in treated animals and presented fewer spermatogonia cells in the allografted testis. In addition, this immunosuppressive therapy was also tested in adult rainbow trout to access the effects on male fertility. Rainbow trout males treated during four-weeks demonstrated lower milt volume, but normal sperm concentration compared to control group. Furthermore, immunosuppressive therapy did not affect the fertilization and hatchling of the progeny produced by the treated males. In summary, this study demonstrated that immunosuppression of the fish host may be a suitable approach to improve reproductive biotechnologies, especially in farther-related species. More importantly, the use of immunosuppressive therapy did not affect spermatogenesis in rainbow trout males and probably does not impair transplanted germ cells and gametogenesis of the treated animals.